Consuming Green Tea at Least Twice Each Day Is Associated with Reduced Odds of Chronic Obstructive Lung Disease in Middle-Aged and Older Korean Adults. Issue 1 (23rd December 2017) - Oh, Chang-Mo; Oh, In-Hwan; Choe, Bong-Keun; Yoon, Tai-Young; Choi, Joong-Myung; Hwang, Jihyen
Abstract: Background: The frequent consumption of green tea has been shown to have antioxidant and anti-inflammatory effects and to reduce the risk of lung cancer and type 2 diabetes. However, few studies have investigated the relation between green tea consumption and the risk of chronic obstructive lung disease (COPD). Objective: This study aimed to examine the association between green tea intake and COPD with the use of a nationwide representative database. Methods: This study was designed as a cross-sectional survey with the use of data from the Korean National Health and Nutritional Examination Survey collected between 2008 and 2015. Of these participants, 13, 570 participants aged ≥40 y were included in the study population. COPD was defined as forced expiratory volume in 1 s (FEV1 ) divided by forced vital capacity (FVC) <0.70. Multiple linear and logistic regression models were used to examine the association between the frequency of green tea intake and risk of COPD after adjusting for age, sex, body mass index, smoking status, alcohol consumption, physical activity, and socioeconomic status. Results: The incidence of COPD decreased from 14.1% to 5.9% with increased frequency of green tea intake from never to ≥2 times/d ( P < 0.001). In the fully adjusted multiple linear regression model, the frequency of green tea intake showed a linear dose-response relation with FEV1 /FVC ( P -trend = 0.031). In the multiple logistic regression model, the OR for COPD among people who consumed green tea ≥2 times/d was 0.62 (95% CI: 0.40, 0.97), compared with those who never drank green tea, after adjusting for all covariates. Conclusion: This study suggests that the consumption of green tea ≥2 times/d is associated with a reduced risk of COPD in Korean populations.